ArtCodes - Baharin, Hanif; Mohd Norowi, Noris; Harun, Afdallyna Fathiyah; Mt Nawi, Khairul Anwar (Universiti Putra Malaysia Press, 2016)
In an experiment with a split brain patient, when the patient’s right brain received a written instruction to stand up, the patient would stand up. But when asked why did he stand up, the patient’s left side of the brain (which control speech) would make up a story that only seems logical to the patient, such as, “I’m standing up to get some water.” This shows the patient’s left side of the brain receives information from the right side unconsciously.